2005
DOI: 10.1385/ir:31:1:25
|View full text |Cite
|
Sign up to set email alerts
|

The Role of B Cells and Accessory Cells in the Neonatal Response to TI-2 Antigens

Abstract: The neonate has an increased susceptibility to infection, in part owing to an inability to produce antibody to thymus-independent antigens such as bacterial polysaccharides (PS). This poor response to PS antigens is likely owing to multiple factors. Neonatal B cells are of an immature phenotype, as evidenced by cell-surface marker characteristics and increased susceptibility to tolerance induction. The spleen of the neonate has a different cellular composition, which is most prominent in the marginal zone. Neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…Moreover, similar to results obtained in the current study with XID B cells, we have shown previously that unlike adult B cells, crosslinking of the BCR on newborn B cells does not increase TACI expression (28). Consequently, as in XID mice, impaired BCR-induced NF-kB pathway activation may be responsible for the severely reduced TACI expression in newborn mice (66,69,71,72). Similarly, both newborn and XID B cell BAFF-R levels are comparable to their respective control mice, suggesting that in both mice, the pathway responsible for controlling BAFF-R expression remains functional and is not dependent on NF-kB.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, similar to results obtained in the current study with XID B cells, we have shown previously that unlike adult B cells, crosslinking of the BCR on newborn B cells does not increase TACI expression (28). Consequently, as in XID mice, impaired BCR-induced NF-kB pathway activation may be responsible for the severely reduced TACI expression in newborn mice (66,69,71,72). Similarly, both newborn and XID B cell BAFF-R levels are comparable to their respective control mice, suggesting that in both mice, the pathway responsible for controlling BAFF-R expression remains functional and is not dependent on NF-kB.…”
Section: Discussionsupporting
confidence: 87%
“…HIS mice up to 6 months of age give the same results (not shown) indicating that the length of the reconstitution period is not a factor. This is reminiscent of human infants and young children that do not respond well to polysaccharide (PS) vaccines [65][66][67]. While the protective antibody response to B. hermsii in mice is a TI response, it is targeted to bacterial surface proteins and is augmented by Toll-like receptor engagement [63,68].…”
Section: B Cell Responses To T Cell-independent Antigens In His Micementioning
confidence: 99%
“…Collectively, these observations lead us to hypothesize that HIS mice generated using our current protocol, like human infants and children [65][66][67], fail to respond to purified PS antigens due to incomplete development of the B cell compartment. In addition, although HIS mice can control B. hermsii infection, they do so less efficiently than wild type mice.…”
Section: B Cell Responses To T Cell-independent Antigens In His Micementioning
confidence: 99%
“…Impaired responses in neonates (9-12 d old) to TI-2 Ags can be attributed to the lack of MZ B cells (8,14). However, 3 to 4-wk-old mice are still unable to respond to TI Ags (7), despite having a developed MZ B cell compartment (Table I).…”
Section: B1b B1a and Mz B Cells Are Present In Young Micementioning
confidence: 99%
“…Similar to young children, young mice under the age of 4 wk are impaired in TI-2 responses (7). Possible factors that may account for the impaired TI responses in the young include defects in B cell activation and the lack of appropriate B cell subsets (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%